Emulgel: A Novel Topical Drug Delivery System - Waghmare, Niranjan D.; Kanchan A. Hiwe,; Ravindra L. Bakal,; Pooja R. Hatwar,; Nagesh G. Khansole,; Umesh S. Saware, (Asian Journal of Pharmaceutical Research and Development, 2025)
Emulgel, a combination of gel and emulsion, is a relatively new and innovative topical medication delivery method with a lot of potential applications in dermatology. An O/W or W/O emulsion is created using gel formulation and specific oils based on their solubility and appropriate emulsifier.Lotions, creams, ointments, and gels are examples of topical treatments that are an essential component of dermatological therapy.Not many notable side effects are present. Emulgel is a very new and creative topical medicine delivery system that combines gel and emulsion and has several potential uses in dermatology. Using gel formulation, particular oils chosen for their solubility, and the right emulsifier, an O/W or W/O emulsion is produced.The present review discusses the method of preparation of emulgel, its permeability across the skin as well as the factors affecting absorption. The evaluation parameters and some marketed formulation also discusses.